PEREMPUAN DALAM SYARIAT ISLAM DAN HAK ASASI MANUSIA - Suyatno Suyatno (Muwazah, 2013)
Abstract : Islam since the beginning of the whole ummah's mandated to protect and put women in a safe position. So that embraces syar'i, women are actually safe and respectable position. But in reality, many obstacles and hurdles that actually invented by the Muslims themselves. The majority of Islamic legal interpretation and the results are written by scholars and men often bring bias in their views. Patriarchal culture has marginalized women, denying women as caliph fil ard, and deny justice teachings promoted by the Qur'an. Ideal-normative Islam does not differentiate between men and women, let alone discriminate against women. As carrier safety and kerahmatan entire universe (rahmatan li al-'aalamiin), Islam puts women's position as evidence of primacy. Women are not appreciated at the time of ignorance, with the arrival of Islam he earned a place of honor, getting an education, open a wider kesempatann for actualization and selfdevelopment. Abstrak : Islam sejak awal seluruh umat yang diamanatkan untuk melindungi dan menempatkan perempuan dalam posisi yang aman. Jadi yang mencakup syar'i, wanita sebenarnya posisi aman dan terhormat. Namun pada kenyataannya, banyak kendala dan rintangan yang sebenarnya diciptakan oleh Muslim sendiri. Mayoritas penafsiran hukum Islam dan hasilnya ditulis oleh ulama dan orang-orang sering membawa bias dalam pandangan mereka. Budaya patriarki telah meminggirkan perempuan, menyangkal perempuan sebagai khalifah fil ard, dan menolak ajaran keadilan dipromosikan oleh AlQur'an. Islam Ideal-normatif tidak membedakan antara pria dan wanita, apalagi mendiskriminasikan perempuan. Sebagai pembawa keselamatan dan kerahmatan seluruh alam semesta (rahmatan li al-'aalamiin), Islam menempatkan posisi perempuan sebagai bukti keutamaan. Wanita tidak dihargai pada saat kebodohan, dengan kedatangan Islam ia mendapatkan tempat terhormat, mendapatkan pendidikan, membuka kesempatann yang lebih luas untuk aktualisasi dan pengembangan diri.